Modelling bank asset quality and profitability: An empirical assessment - Vighneswara Swamy (Kiel Institute for the World Economy (IfW), 2015)
The determinants of default risk of banks in emerging economies have so far received inadequate attention in the literature. This paper seeks to study the determinants of bank asset quality and profitability using panel data techniques and robust data sets for the period between 1997 and 2009. The study findings reveal some interesting results that run contrary to established perceptions. Priority sector credit has been found to be not significant in affecting NPAs; this is contrary to the general perception. Similarly, with regard to rural bank branches, the results reveal that aversion to rural credit is a falsely founded perception. Bad debts are dependent more on the performance of industry than on other sectors of the economy. Public sector banks have shown significant performance in containing bad debts. Private banks have continued to be stable in containing bad debts, as they have better risk management procedures and technology, which definitely allows them to finish with lower levels of NPAs. Further, this study investigates the effect of determinants on profitability, and establishes that while capital adequacy and investment activity significantly affect the profitability of commercial banks, apart from other accepted determinants of profitability, asset size has no significant impact on profitability.
Keywords: G21; G28; G32; E44; E58; 330; banks; risk management; ownership structure; financial markets; non-performing assets; lending policy; macro-economy; central banks; banking regulation; financial system stability